2019
DOI: 10.1017/s1092852919001615
|View full text |Cite|
|
Sign up to set email alerts
|

The broad autism phenotype in real-life: clinical and functional correlates of autism spectrum symptoms and rumination among parents of patients with autism spectrum disorder

Abstract: Objective. Increasing literature reported higher rates of psychiatric disorders in parents of children with autism spectrum disorder (ASD), as well as of autistic-like features in social and cognitive functioning. However, little attention has been paid to the association between autistic traits (AT) and global functioning in this population. The aim of the present work was to investigate clinical and functional correlates of AT among parents of ASD children, with a specific focus on ruminative thinking. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 100 publications
4
65
0
Order By: Relevance
“…They reported that the strongest predictors of suicidality score were restricted interests and the rumination domain score of autistic traits. Carpita et al 16) reported that the effect of autistic traits on social and occupational functioning was totally mediated by the presence of ruminative thinking, and indicated that mental rumination involves perseverative thoughts that revolve around a negative emotion or situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that the strongest predictors of suicidality score were restricted interests and the rumination domain score of autistic traits. Carpita et al 16) reported that the effect of autistic traits on social and occupational functioning was totally mediated by the presence of ruminative thinking, and indicated that mental rumination involves perseverative thoughts that revolve around a negative emotion or situation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Dell’Osso et al 15 ) reported that restricted interests and rumination domain scores on the Adult Autism Subthreshold Spectrum (AdAS) were associated with suicidality in patients with full-blown ASD and subjects with autistic traits, as well as in a healthy control group. Carpita et al 16 ) found that AdAS nonverbal communication domain scores were a statistically predictive variable for the presence of psychiatric disorders among 120 parents of ASD children. Furthermore, Takara and Kondo 17 ) extracted four indicators (interpersonal friction, experience of being bullied, psychotic-like experiences, age under 32 yr) that distinguished people with ASD from depressive adults.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, a wide number of research has highlighted how clinical ASD should be considered the extreme end of a continuum of behavioral and cognitive features, distributed in the clinical and general population, where they are often being labeled as “autistic traits” [ 3 , 4 ]. The concept of autistic traits, according to the most recent studies, refers to a range of milder manifestations, qualitatively similar to the core features of ASD (such as subthreshold social and communication impairments, unusual personality features and stereotyped behaviors), which were frequently reported among unaffected relatives of people with autistic conditions [ 5 ]. Autistic traits were firstly noticed and investigated among parents of children with ASD, leading to the conceptualization of a Broad Autism Phenotype (BAP) [ 6 , 7 ], and further stressing the presence of a continuum between clinical and subthreshold manifestations of the autism spectrum even from a genetic and neurobiological point of view [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It allows parents to establish a positive parenting style by being thoughtful and empathic, which in turn decreases their children's problem behaviours (Singh et al 2006(Singh et al , 2014. Also, previous studies have shown parents of children with ASD experience higher levels of stress, rumination, and poorer well-being than parents of children with typical development (Bonis 2016;Carpita et al 2019;Giallo et al 2013;Lai et al 2015;Wang et al 2013). Providing mindfulness training could help them alleviate these problems and reduce their burdens.…”
Section: Introductionmentioning
confidence: 99%